Position-parameter selection criterion for a helix-curve meshing-wheel mechanism based on sliding rates - Ding, Jiang (Strojniški vestnik, 2014)
The space curve meshing wheel (SCMW) is an innovative gear mechanism mediating transmission between space curves instead of classic space surfaces; the most common type of SCMW is the helix curve meshing wheel (HCMW). In this study, we propose a position-parameter selection criterion of the HCMW based on its slide rates. The sliding rates of the contact curves at the meshing point are defined and calculated; the optimal meshing condition of the HCMW is attained by analyzing the features of the slide rates; the position-parameter selection criterion is subsequently attained as well as corresponding contact curve equations. Both simulation and practical examples using different position- parameters are provided to verify the transmission continuity, and their slide rates are calculated. The calculating result shows that the HCMW coincident with the position-parameter selection criterion has better slide rates and, therefore, can have better tribological performance. The design method proposed in this paper aims to change the current situation so that the position-parameters of the HCMW are determined according to designers' experience, and theoretically provides a foundation for its standardized production in industry.
Keywords: drsna stopnja; izbira parametrov; parameter položaja; prostorske krivulje; ubirnica v obliki vijačnice; zobniki